UNLOCKING YOUNG MINDS: THE POWER OF STORYTELLING IN TEACHING ENGLISH FOR YOUNG LEARNERS - Isnaniah Isnaniah; Tenia Ramalia; Intan Viona; Livia Luthfiyandini; Tifana Belina (PRIMACY Journal of English Education and Literacy, 2024)
This article will explain the power of storytelling in teaching English to young learners. Utilizing stories for scholastic purposes is a very useful system for teaching English to young learners. Storytelling is one of the main support systems for engaging young learners in the learning process. Storytelling has a good chance for young learners to discover the experience of real life and the language learning experience together. Through stories, young learners can gain various abilities and skills to develop themselves in English. Most young learners like stories; therefore, implementing English through stories gives strength to young learners.